Synthesis of poly(l-lactic acid)-hydroxyapatite composite as material for 3d printing of bone tissue growth stimulating implants; 6th International Congress on Energy Fluxes and Radiation Effects; 3rd International Conference on New Materials and High Technologies (3rd NMHT), November 2018 - Dubinenko G. E. Gleb Evgenjevich (2018, 2018)
Title screen